Low back pain presentations to New South Wales emergency departments: Trends over time and geographical variation. (22nd February 2021) - Ferreira, Giovanni E; Herbert, Rob; Machado, Gustavo C; Richards, Bethan; Harris, Ian A; O'Keeffe, Mary; Zadro, Joshua R; Maher, Chris G
Abstract: Objective: To determine whether rates of ED presentations because of low back pain (LBP) have increased from 2016 to 2019 in New South Wales and map the geographical distribution of ED presentations because of LBP across New South Wales. Methods: We sourced data from the New South Wales Emergency Department Records for Epidemiology. We included all ED presentations aged 15 years and older with a diagnosis of LBP to the 178 public EDs across New South Wales from 1 January 2016 to 31 December 2019. We calculated the ratio (95% confidence interval) between the 2016 and 2019 age‐standardised rates to determine whether an increase in the rate of ED LBP presentations has occurred. To assess geographical variation, we aggregated presentations by their home postcode. We calculated age‐standardised rates per 100 000 person year for each of those areas using data from 2016 to 2019. Results: We included 188 275 LBP presentations for patients aged 15 years or older. Their mean (standard deviation) age was 51.3 (20.0) years. From 2016 to 2019, we observed a 5.3% increase in the age‐adjusted LBP ED presentation rates (age‐standardised ratio 1.05, 95% confidence interval 1.04–1.06). We found a 20‐fold variation in LBP ED age‐standardised presentation rates across the different local government areas of New South Wales. Higher rates were mostly observed in rural and regional areas. Conclusions: The demand for ED services because of LBP has increased in New South Wales over time, and we observed a 20‐fold variation in presentation rates across different regions. Abstract : The demand for emergency services among people with low back pain in public emergency departments in New South Wales is increasing over time. There is a 20‐fold variation in the rates of low back pain presentations to emergency departments across different regions of New South Wales.